PERANCANGAN PERKERASAN PADA PERLUASAN APRON BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Elga Apriadha Dwinata; Indartono Rivai (FTSP Universitas Jayabaya, 2022)
The high movement of aircraft at I Gusti Ngurah Rai International Airport in Bali, has not beenmatched by adequate airside facilities, especially on the apron, which has resulted in mobilization not going well. This underlies the need for an expansion of the apron in order to fulfill the capacity of the aircraft that will operate. The aim is that the planned number of aircraft stands can meet the needs of aircraft operating during peak hours, with reference to the dimensions and pavement of the apron in accordance with civil aviation safety regulations standards so that aircraft mobilization can run well. For this reason, it is necessary to plan to expand the apron with a qualitative descriptive analysis method, namely in principle every matter of the problems raised must be answered in the data analysis by linking one another or in other words there is a reciprocal relationship, in this case the calculation method used is the method FAA (calculations manually and using software). Based on the analysis and calculations using this method, the results obtained from the analysis of the number of aircraft movements and the number of aircraft stands needed in the plan year with a pavement thickness that is in accordance with the standard airport requirements referring to the critical type of aircraft operating, so that the number of aircraft movements during rush hours can be overcome.